Parametric Investigation Of SF6 Gas Mixtures For Ring Main Unit (RMU) Switchgear Application - Zainuddin, Hidayat; Aman, Aminudin; Sutan Chairul, Imran; Kamarudin, Muhammad Saufi; Mohd Wari, Jamaludin (UTeM, 2020)
In high voltage applications, sulphur hexafluoride (SF6) gas has been utilized as the electrical insulation and/or current interrupter due to its strong electronegative properties. However, in Kyoto Protocol 1997, SF6 has been recognized as one of the greenhouse gases which contribute to the global warming issues, thus need to regulate its usage and emission to the atmosphere. As one of the effort to minimize the usage of SF6, this research project conducts the investigation on the breakdown behavior of SF6 gas mixtures (i.e. SF6/N2 and SF6/CO2), specifically for ring main unit (RMU) switchgear application. In order to examine the breakdown behavior of the SF6 gas mixtures, a series of breakdown voltage test were conducted under AC voltage stress at pressure range between 1.1 bar to 1.5 bar, which is typically used for this type of switchgear. In this research, the SF6 content in both SF6 gas mixtures was varied between 10 % to 30 %. On the other hand, two types of electrodes configurations were used (i.e. R0.5-plane and R6-plane) to represents different non-uniform field condition during the breakdown voltage test, where the gap distance between the electrodes was varied from 5 mm to 30 mm. As a function of SF6 gas mixture ratio, the results show that the mean AC breakdown voltage (Ua) values of SF6/N2 and SF6/CO2 gas mixtures at all pressure levels increases when the SF6 content in the gas mixture is increased. However, the Ua value increment of SF6 gas mixtures is found to be less significant when the amount of SF6 amount is increased above 10 %. By focusing on the gas mixture ratio with 10 % amount of SF6, it was observed that the Ua values of SF6/N2 (10/90) and SF6/CO2 (10/90) gas mixtures under both electrode configurations increase with the increase of gas pressure and electrodes gap distance. Between these two effects, the analysis of variance (ANOVA) results obtained from multiple regression analysis have shown that the electrode gaps distance gives the most significant effect to cause the Ua values of SF6/N2 (10/90) and SF6/CO2 (10/90) gas mixtures to increase compared to gas pressure, due to its high percentage of contribution. In addition, the comparison between the Ua values of SF6/ CO2 (10/90) and SF6/N2 (10/90) have been made and it was found that the Ua values of SF6/CO2 (10/90) are higher than SF6/N2 (10/90), especially under high electric field non-uniformity. In this research, the electric field behavior under R0.5-plane and R6-plane configurations has been investigated using COMSOL Multiphysics software. The simulation results show that a more non-uniform electric field exists between the electrodes when R0.5-plane is used compared to R6-plane and the electric field non-uniformity between the electrodes increases with the increasing gap distance. This indicates that SF6/CO2 (10/90) perform better than SF6/N2 (10/90) in suppressing the breakdown streamer when high non-uniform electric field exists between the electrodes. Lastly, it was observed that although with 10 % amount of SF6, the Ua values of SF6/N2 and SF6/CO2 gas mixtures could reach about 48 % and above as relatives to pure SF6, throughout all gap distances and pressure levels under both electrode configurations.